Financial Disruption and Psychological Underpinning During COVID-19: A Review and Research Agenda - Singh, Sanjeet; Bedi, Deepali (Frontiers in Psychology, 2022)
COVID 19 has disastrous impacts on sustainability initiatives and worsened poverty, hunger, and health issues. The financial distress by this pandemic has resulted in psychological challenges among the people. The list of vulnerable sections of the psychological impacts of the financial problems during COVID 19 is led by students, pregnant women, children, old age people, parents, and many more. The recommendations of this paper are to focus on coping strategies for managing psychological issues related to financial problems during the pandemic, facilitating social support, promoting public health facilities and health insurance, financial support for pregnant women, and child care. Special care for old age people and support for troubling parents and students. This paper also recommends interventions and policies for reviving the disrupted businesses and strengthening entrepreneurs, Measures for income generation, removal of hunger, and reducing addictions and gambling should also be on the priority list. Limited collaboration among countries was observed, but robust collaboration among the research institutions and authors.